Economic and Legal Considerations of Optimal Privatization : Case Studies of Mortgage Firms (DePfa Group and Fannie Mae) - Garrett, John.; Beyer, Hans-Joachim.; Dziobek, Claudia (Washington, D.C. : International Monetary Fund, 1999)
Successful privatization must be accompanied by the complete removal of privileges and any public policy mission. Bank behavior changes rapidly as profit maximation replaces the bureaucratic objective function. Once privileges are granted, they are difficult to remove. Therefore, privatization is a one-time (nonreversible) operation. The German mortgage bank, DePfa, went through a carefully planned and lengthy privatization process that was successful. Fannie Mae, the U.S. mortgage firm, became a privately owned institution endowed with special privileges, which led to a quasi-monopoly position. This resulted in suboptimal financial sector performance. Fannie Mae's special privileges have proven resistant to reform efforts.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet